Perception in action - Giorello, Giulio; Sinigaglia, Corrado (Acta Biomedica Atenei Parmensis, 2007)
For long time perception and action have been considered as separated and peripheral processes, devoid of any intrinsic cognitive value. Over the last years, however, this view has been challenged by several neurophysiological data. The aim of this paper is to provide an overview of some recent studies on the cortical visual and motor systems. In particular, we’ll focus on the discovery (in the inferior parietal lobe and in the premotor cortex) of two different kinds of sensorimotor neurons that not only are involved in the motor control of actions, but also play an essential role in object categorizing and in action understanding.We’ll argue that the functional properties of these kinds of neurons show the limits and abstractness of any strict dichotomy between perception and action, and pave the way to a requalification of some relevant philosophical perspectives on these issues.